Analisis Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Kosmetik Wardah pada Department Store Kota Malang - Safira Angelina, Intan; Widiawati, Diah (University of Merdeka Malang, 2022)
Cosmetics are never separated from one's efforts to beautify oneself and improve the quality of one's appearance. One of the cosmetic brands currently circulating in the market is Wardah brand cosmetics. This study is intended to (1) describe product quality, price and purchasing decisions (2) analyze the extent to which the influence of product quality and price on purchasing decisions, both simultaneous and partial analysis (3) analyze the variables that have the greatest influence on purchasing decisions with a sample of a number of 80 respondents through accidental sampling technique. The analysis technique used is descriptive analysis, multiple linear regression, and also hypothesis testing (F and t test). Based on the results of the analysis simultaneously or partially, the two independent variables, namely product quality and price, have a significant influence on purchasing decisions. Meanwhile, price is the most influential variable in Wardah's cosmetic purchasing decisions.